Re-Interpreting The Catholics’ Images of the Church in Java – Part I - Tedjoworo, Hadrianus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2012)
This article is an endeavour to be ‘imagerially present’ among the believers in Java, and in this way, could add to the sensitivity to what is happening in the praxis of faith of the Catholics in Java. Christian faith may have caused some changes in the believers’ imagination. Catechesis on the church in Java can take many advantages from this research, considering that its outcome comprises of the church images which can be used to enhance the catechetical material. The distinction of images appears in four dimensions (the believers’ imagerial preferences, the church’s relevance, the believers’ intentions to participate and their contextual and meaningful images). This research is an opening towards further reflections about ‘imagerial catechesis’ in Java. In this eye, it prepares a necessary path for deepening the conviction that the believers’ ‘cultural’ ways of being church are an essential element in the process of doing theology with images. No less than seventeen images have surfaced during the efforts of re-imagining the church images. These ‘cultural’ and communal images are correlated with the ‘biblical’ images of the church in order to unearth the believers’ interpretations of the latter within the sociocultural contexts.